Effect of cropping technologies on the yield of dry bean variety ’Diana’ - Györgyi, Gyuláné; Henzsel, István; Ferenczy, Antal (Acta Agraria Debreceniensis, 2016)
An experiment on three dry bean varieties (Start, Hópehely, Diana), using different sowing-times, fertilizers and plant densities was performed on sandy soil in the University of Debrecen, Centre for Agricultural Sciences, Research Institute of Nyíregyháza in 2015. The aim of the experiment was to study which treatment gives the highest yield, and whether the different treatments result in significant differences in the yields. In this paper the dry bean yield at ‘Diana’ variety is analyzed. The treatments were done with three fertilizer doses and three plant densities at different sowing-times (April 24; May 8; May 18). As a result of the high temperature and the drought during the growth season, the yields we harvested were in low, which shows the ecological sensitivity of the plant we examined. We concluded that the poorest yield was harvested at the third sowing-time. There was no significant difference in the yields at the first and second sowing- time. Examining all the three fertilizer treatments we applied at the experiment, we achieved the highest yields in the control plots. It might be due to the weak efficiency of nitrogen fertilizer under the extremely dry conditions. The highest yield was harvested at the control treatments during the second sowing-time. Regarding the effect of the plant densities, the highest crop yield was achieved at the treatment using 400 000 germs ha-1, followed by 300 000 germs ha-1 and 200 000 germs ha-1.